Innis and the news - Babe, Robert E. (Javnost (Ljubljana), 2006)
Long neglected internationally, the media scholarship of Canadian economic historian and political economist Harold Adams Innis (1894-1952) has in recent years been taken up, largely without attribution or acknowledgment, by writers focusing on media as a key factor in social/political/ cultural evolution, by dependency theorists (media or cultural imperialism writers), and (ironically) by postmodernists/ poststructuralists. This article first provides an overview of Innis's two main fields, his staples thesis of Canadian economic development, and media thesis as it concerns world history. This section also relates the media thesis to contemporary media and dependency theories and postmodernist discourses. The second focus of the article is on Innis's critical analysis of press systems. The discussion not only integrates his staples and media theses, buy also extrapolates Innis's analysis to the present to show the deep concerns he would express regarding the present-mindedness of contemporary media and culture. Throughout there is an emphasis on Innis's materialist understanding of culture and social relations.
Keywords: Innis, Harold Adams, 1894-1952; sociološke teorije; mass media; množični mediji; printing; tisk; komuniciranje; communication; sociologija komunikacij